2021
DOI: 10.1002/2211-5463.13176
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cytochrome c shot towards histone chaperone condensates in the nucleus

Abstract: Despite mitochondria being key for the control of cell homeostasis and fate, their role in DNA damage response (DDR) is usually just regarded as an apoptotic trigger. However, growing evidence points to mitochondrial factors modulating nuclear functions. Remarkably, after DNA damage, cytochrome c (Cc) interacts in the cell nucleus with a variety of well-known histone chaperones, whose activity is competitively inhibited by the hemeprotein. As nuclear Cc inhibits the nucleosome assembly/disassembly activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 278 publications
(423 reference statements)
0
3
0
Order By: Relevance
“…In addition, C c has been shown to be released from mitochondria and translocate into the nucleus under DNA damage conditions. [ 6 , 16 ] Although the nuclear role of C c is not fully understood, it has recently been shown that following DNA breaks, C c specifically interacts with SET/TAF‐Iβ, [ 6a ] and NAP1‐Related Protein 1 (NRP1), [ 6b ] a plant homologous of SET/TAF‐Iβ, acting as a histone chaperone inhibitor. Therefore, we decided to include C c in our single‐molecule kinetic experiments to challenge the relevance of the chaperone activities reported in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, C c has been shown to be released from mitochondria and translocate into the nucleus under DNA damage conditions. [ 6 , 16 ] Although the nuclear role of C c is not fully understood, it has recently been shown that following DNA breaks, C c specifically interacts with SET/TAF‐Iβ, [ 6a ] and NAP1‐Related Protein 1 (NRP1), [ 6b ] a plant homologous of SET/TAF‐Iβ, acting as a histone chaperone inhibitor. Therefore, we decided to include C c in our single‐molecule kinetic experiments to challenge the relevance of the chaperone activities reported in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The translocation of cyt c to the nucleus was also reported after the induction of DNA damage and after treatment with proapoptotic agents, although there is no information regarding cyt c conformation ( 44 47 ). The functions of accumulated cyt c in the nucleus following apoptotic stimuli are related to nuclear pyknosis, DNA fragmentation, and chromatin remodeling ( 44 , 45 ).…”
mentioning
confidence: 99%
“…It was previously shown that cyt c interacts with several histone chaperones, as is the case for the oncoprotein SET/TAF-Iβ. This interaction impairs the histone chaperone activity and prevents the formation of the core histone complex ( 46 48 ). These results suggest a wider role of cyt c in DNA damage response independent caspase activation.…”
mentioning
confidence: 99%